2005
DOI: 10.3233/jad-2005-8305
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aβ42 correlates positively with increased body fat in healthy individuals

Abstract: Abstract. Obesity and overweight, well known risk factors for cardiovascular disease and type 2 diabetes, are now associated with Alzheimer's disease (AD). It remains to be determined if obesity and overweight contribute to the risk of developing AD through modulating levels of amyloid-beta (Aβ), a key molecule in AD pathogenesis. Thus, we investigated whether there were any associations between plasma Aβ levels and body mass index (BMI) or fat mass (FM) in a group of 18 healthy adults. A statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 80 publications
4
53
1
Order By: Relevance
“…76 Thus RAGE plays a direct and indirect role in AD pathogenesis, in particular, the apparent inverse relationship between sRAGE and cholesterol may add yet another modulatory effect on Ab metabolism as cholesterol is a known mediator of inflammation and APP processing. [93][94][95][96][97][98][99][100][101][102][103][104] Efflux of Ab: LRP-1/Ab interactions at BBB LRP-1 is a multi-ligand lipoprotein receptor involved in the mediation of endocytosis or activation of signalling molecules for a diverse range of secreted and membrane-bound ligands. Receptor activating protein (RAP) is a 39 kDa chaperone protein that binds to LRP-1 and regulates its tertiary structure.…”
Section: Influx Of Ab Rage/ab Interactions At Bbbmentioning
confidence: 99%
“…76 Thus RAGE plays a direct and indirect role in AD pathogenesis, in particular, the apparent inverse relationship between sRAGE and cholesterol may add yet another modulatory effect on Ab metabolism as cholesterol is a known mediator of inflammation and APP processing. [93][94][95][96][97][98][99][100][101][102][103][104] Efflux of Ab: LRP-1/Ab interactions at BBB LRP-1 is a multi-ligand lipoprotein receptor involved in the mediation of endocytosis or activation of signalling molecules for a diverse range of secreted and membrane-bound ligands. Receptor activating protein (RAP) is a 39 kDa chaperone protein that binds to LRP-1 and regulates its tertiary structure.…”
Section: Influx Of Ab Rage/ab Interactions At Bbbmentioning
confidence: 99%
“…We found a significant positive correlation of HDL levels with Aβ 1-42 levels among statin nonusers. Similarly, a previous study evaluating plasma Aβ 1-42 among 18 healthy individuals found a correlation between HDL and Aβ (35). However, Mayeux and colleagues reported an association of HDL with Aβ 1-40 instead (2).…”
Section: H I G H a β I N R E L A T I V E S O F A D P A T I E N T Smentioning
confidence: 81%
“…[115][116][117] Obese men have been found to have lower cognitive function when compared with non-obese normotensive men, 115 and in an 18 year follow-up study in overweight women, a high risk for dementia (particularly AD) was found in these women relative to controls. 116 In our own recent studies, we have observed a strong positive correlation between body fat and blood Ab1À42 levels in cognitively normal individuals, 118 and in a recent longitudinal study of 1149 individuals, mid-life obesity was found to be a significant risk factor for AD later in life. 119 This association has now also been linked to hyperinsulinemia: insulin infusion (inducing temporary hyperinsulinemia) increases blood plasma Ab1À42 levels in cognitively normal individuals who are offspring of AD patients: and the magnitude of Ab1À42 increase is greater in subjects with increased abdominal body fat.…”
Section: Statins and Admentioning
confidence: 85%